PHYSICIAN CAREER SATISFACTION WITHIN SPECIALTIES IN ERBIL CITY - Banna, Haitham Issa Bahoo Al- (Journal of Sulaimani Medical College, 2022)
Background Doctors’ satisfaction with their careers and lifestyle is of considerable importance since it affects their healthcare providers and may influence the chosen specialty of the upcoming doctors. It is affected by many factors and varies among different specialties. Objectives To determine the level of satisfaction among different specialties and the factors influencing their satisfaction.t Subjects and Methods A cross-sectional study was carried on 2019 among 170 specialists from Hawler Medical University/college of medicine, four governmental hospitals, and two online Facebook groups by distributing two forms of a selfadministered questionnaire, a hard copy and an online form. The randomly distributed questionnaire included doctors’ socio-demographic data, specialty, and lifestyle. SPSS was used for data analysis, Chi-square and Fisher exact test as appropriate was used, P-value to be significant at ≤0.05 Results Of the 170 participating doctors, 68.8% were males. About thirty-four percent were medicine specialists, and twenty percent were from the surgical field. Eighty percent said that they were happy during working time. This study also revealed that surgeons do not give their families enough time 26.5%. About twenty percent reported they are stressed most of the time, while 64.1% are only sometimes stressed, of whom radiologists (33.3%) are the least stressed. About sixty percent of specialists chose their specialty because of personal interest, in 79.4% of surgeons were with them. In contrast, 21.8% of doctors chose it because it was the best available for them, of whom 52.9% were gynecologists. Nearly fifty-nine percent of physicians reported being very satisfied, and 16.5% were extremely satisfied, with specialty having no significant effect. Conclusion Satisfaction varies by specialty. Personal interest was the main factor in choosing a specialty, most doctors were happy during working time, and they agreed on “more free time” to be more satisfied.
Keywords: Stress; Physician satisfaction; Job satisfaction; Doctor-patient relationship